An overview of the Qur'anic system of education in Nigeria and Malaysia - Alkali, Alhaji Umar; Che Soh @ Yusoff, Roslina; Abdul Hak, Nora (The Department of Arabic and Islamic Studies, University of Maiduguri, 2016)
The practice in most Muslim societies is to introduce children to memorization of the Qur'an at the early stage of their lives. In Nigeria and Malaysia, both formal and informal schools function in order to impact this important treasurer to children. The alMajiri system of Qur'anic education is used as the traditional informal school system in Nigeria for the purpose of memorization of the Qur'an, unfortunately, due to lack of proper management and planning, this system of education has become a breeding ground for miscreants in the society. A formal system of education where both Qur'anic and Western systems of education is concurrently taught has in recent years gained acceptance especially from parents that want to 'kill two birds with a single stone'. This article tries to examine the two systems of Qur'anic education in Nigeria and Malaysia, the challenges facing the systems and suggests how best these challenges can be addressed so that the systems can be a source of pride for the ummah.